A Priori Property Estimation of Physical and Reactive CO2 Absorbents - Völkl, Johannes; Müller, Karsten; Mokrushina, Liudmila; Arlt, Wolfgang (Chemical Engineering & Technology, 2012)
The physical as well as the chemical solubility of carbon dioxide in several ionic liquids were predicted with quantum chemical a priori methods. The physical solubility was described with the model COSMO-RS. The results were compared to experimental data. Both a qualitative and based on the concept of relative solubility quantitative benchmark for the solvents were possible. For the part of chemical absorption, the free reaction enthalpy, ?Rg, and reaction enthalpy, ?Rh, were determined with DFT calculations on the B3LYP/def2-TZVPP level. By combining reaction and phase equilibrium, the CO2 loading of the reactive solvents were predicted. The results were validated with literature data. An approach was developed for a quantitative a priori description of both physical and chemical solvation of CO2.
Keywords: Carbon dioxide; Ionic liquids; Prediction; Reactive absorption